Cara Berpikir Seorang Wirausahawan Sukses untuk Menciptakan Peluang Bisnis - Ferdi Eka Darma; Walde Mesah; Yosia Bello (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Along with the times and advances in technology, entrepreneurship has become an important pillar in economic growth. Entrepreneurship not only creates jobs, but also utilizes existing natural resources effectively. However, many people fail in starting a business because of the wrong mindset, a sense of personal limitations, and an inability to adapt to changing times. This article discusses the importance of having the right mindset, or mindset, in running a business. A growth mindset, which describes the belief that intelligence and skills can develop through effort and experience, is considered essential for entrepreneurial success. Meanwhile, a fixed mindset that views ability as something that is fixed can hinder progress. A positive and optimistic mindset is a key factor in facing entrepreneurial challenges. Entrepreneurs who think positively tend to see difficulties as opportunities to learn and grow, while those who are optimistic have higher motivation and are more resistant to pressure. Apart from that, creativity and innovation are aspects that are no less important, because entrepreneurs must be able to create products or services that can meet market needs and adapt to changes. Entrepreneurship also requires mental perseverance to face failure and unexpected challenges. A successful entrepreneur must have a tenacious, creative, hardworking attitude and dare to take risks. With a combination of these traits, entrepreneurs can achieve long-term success in their businesses. This article emphasizes that the right mindset, coupled with an innovative attitude and perseverance, greatly influences the journey and success of an entrepreneur.